Distributed power flow controller based on fuzzy-logic controller for solar-wind energy hybrid system - Vemuri Sowmya Sree; Coppisetty Srinivasa Rao (International Journal of Power Electronics and Drive Systems (IJPEDS), 2022)
The demand of electricity globally led to the concept of renewable energy resources for power generation that are eco-friendly and freely available from nature. The solar photovoltaic systems and wind-based power generators are considered as primary renewable resources and are called as Distributed Generation units as they are scattered in nature. These are operated with bidirectional converters by providing auxiliary services at grid side and load side in either mode of microgrid operation. Besides, the DC power generation units’ integration gets converted into AC system by means of inverters.  These types of systems not only increase voltage and current harmonics, power frequency deviations but also drive the distribution system to risky operating zone. This emphasizes the stipulation of advanced control schemes for microgrid architecture. Consequently, power electronic converters introduce harmonics in the system and affect the system performance. To report these expanded issues, the authors recognized an advanced custom power device entitled distributed power flow controller. The proposed hybrid solar-wind energy system is first studied with a distributed power-flow controller. Later the system is examined by replacing proportional integral controller with fuzzy logic controller (FLC) for shunt control of distributed power-flow controller. To validate the investigations, MATLAB/Simulink software is used.